Novel avenues for treating diabetic nephropathy: new investigational drugs. (3rd April 2017) - Lacava, Viviana; Pellicanò, Vincenzo; Ferrajolo, Carmen; Cernaro, Valeria; Visconti, Luca; Conti, Giovanni; Buemi, Michele; Santoro, Domenico
ABSTRACT: Introduction : At present, treatment of diabetic kidney disease (DKD) is still mainly based on drugs acting on glycemic and blood pressure control, as there is no validated therapy able to halt the progression of renal failure. Because of the high incidence of DKD, due to the increase of diabetes mellitus in general population, new therapeutic strategies are needed. Areas covered : We analysed ongoing and already completed clinical trials, from clinicaltrials.gov and PubMed, dealing with new therapies for DKD. Expert opinion : Among the drugs currently being explored, the most promising molecules are those that interfere with glucose-dependent pathways, in particular polyol, protein kinase, hexosamine and AGEs metabolic pathways, and impaired renal vascular regulation. One of the recent goals achieved by molecular biology is the development of monoclonal antibodies able to interfere with extracellular matrix accumulation and fibrosis. Other interesting therapies are under investigation and further studies with a greater number of patients will establish a better approach for diabetic nephropathy.